2014
DOI: 10.1017/s071498081400021x
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Interprofessional Working of a Home-Based Primary Care Team

Abstract: Increasingly, interprofessional teams are responsible for providing integrated health care services. Effective teams, however, are not the result of chance but require careful planning and ongoing attention to team processes. Based on a case study involving interviews, participant observation, and a survey, we identified key attributes for effective interprofessional working (IPW) within a home-based primary care (HBPC) setting. Recognizing the importance of a theoretical model that reflects the multidimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 70 publications
(107 reference statements)
1
40
0
Order By: Relevance
“…Frequently mentioned favourable factors are: shared vision, common goals, respect and trust among team members, communication, effective leadership, shared reflection (12,14,15) and a clear description of roles and responsibilities (17). A review by Xyrichis and Lowton (2008) revealed that team processes as well as team structure impact on successful IPT meetings in a primary care setting (14).…”
Section: Introductionmentioning
confidence: 99%
“…Frequently mentioned favourable factors are: shared vision, common goals, respect and trust among team members, communication, effective leadership, shared reflection (12,14,15) and a clear description of roles and responsibilities (17). A review by Xyrichis and Lowton (2008) revealed that team processes as well as team structure impact on successful IPT meetings in a primary care setting (14).…”
Section: Introductionmentioning
confidence: 99%
“…Examples of the translated key metaphors and corresponding overarching themes are presented in Table . The overarching themes fell in a pattern of team forming and development and are presented in an order organised as such (Smith‐Carrier & Neysmith, ).…”
Section: Resultsmentioning
confidence: 99%
“…Team unification was regarded as a necessary process for team cohesion and to proceed to further team development and accomplishing set tasks. This theme often manifested itself in the form of comments by professionals surrounding a shared or common vision that necessitated trust in a safe and supported environment (Anderson, Pollard, Conroy, & Clague‐Baker, ; Jones & Jones, ; Légaré et al, ; Smith‐Carrier & Neysmith, ; Smith‐Carrier et al, ). Another major aspect of this theme was the “respect for professionalism” and the recognition that there needed to be one team member in charge, but that each interdisciplinary team member brought the “best knowledge and experience” to the discussion of the care plan for the older person (Birkeland, Tuntland, Førland, Jakobsen, & Langeland, ; Smith‐Carrier et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations